Bioactive Phosphate Glasses - Lapa, Agata (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2018)

Correction: Ga and Ce ion-doped phosphate glass fibres with antibacterial properties and their composite for wound healing applications (Journal of Materials Chemistry B (2019) DOI: 10.1039/c9tb00820a) - Lapa, Agata; Cresswell, Mark; Campbell, Ian; Jackson, Phil; Goldmann, Wolfgang; Detsch, Rainer; Parsons, Andrew; Ahmed, Ifty; Boccaccini, Aldo R. (Journal of Materials Chemistry B, 2019)
The authors regret that in the original article the affiliation list is presented incorrectly. The corrected list is shown above. This change does not affect the affiliation tags used in the author list, which therefore remain the same. The Royal Society of Chemistry apologises for these errors and any consequent inconvenience to authors and readers.
CRIS-Team Scopus Importer:2019-12-03

Ga and Ce ion-doped phosphate glass fibres with antibacterial properties and their composite for wound healing applications - Lapa, Agata; Cresswell, Mark; Campbell, Ian; Jackson, Phil; Goldmann, Wolfgang; Detsch, Rainer; Parsons, Andrew; Ahmed, Ifty; Boccaccini, Aldo R. (Journal of Materials Chemistry B, 2019)
Novel gallium/cerium-doped phosphate glass fibres (PGF) were successfully manufactured by the melt-quenching and melt-spinning process. The amorphous character of the materials produced was confirmed using X-ray powder diffraction (XRD), and the elemental composition was investigated with X-ray fluorescence confirming the presence of 2 mol% of Ga2O3 or CeO2. Fourier Transform Infrared Spectroscopy (FTIR) confirmed the presence of Q1 and Q2 structural phosphate species. Mechanical properties of the PGFs revealed tensile strength values of 428 ± 94 MPa and 379 ± 80 MPa, with elastic modulus values of 45 ± 4 GPa and 54 ± 9 GPa for Ce-PGF (diameter 25 μm) and Ga-PGF (diameter 18 μm), respectively. The influence of both dopants on the glass degradation properties was evaluated by tests in deionised water, which revealed a decreased dissolution rate for gallium-doped PGF in comparison to cerium-doped PGF. Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) measurements were used to explore ion release in cell culture medium, while ICP-mass spectrometry (ICP-MS) was used to measure ion release in deionised water. These techniques showed controlled release of therapeutic and antibacterial ions from the PGF. Antibacterial properties of Ce-PGF and Ga-PGF, based on turbidity measurements, were confirmed against Gram-positive bacteria. Moreover, Ce-doped phosphate glass fibres did not disturb the proliferation of human epidermal keratinocyte (HaCaT) cells or the mobility of mice embryonic fibroblasts (MEF). Applying an in vitro scratch assay showed full wound closure after 24 h of indirect incubation with Ga-PGF. Due to their superior processability as compared with Ga-PGFs, a fully degradable mesh based on Ce-PGF was designed and found to achieve high water uptake (up to 800%), suggesting its suitability for wound healing applications.
CRIS-Team Scopus Importer:2019-11-22

Gallium- and Cerium-Doped Phosphate Glasses with Antibacterial Properties for Medical Applications - Lapa, Agata; Cresswell, Mark; Campbell, Ian; Jackson, Phil; Goldmann, Wolfgang H.; Detsch, Rainer; Boccaccini, Aldo R. (Advanced Engineering Materials, 2020)
Novel cerium- (Ce) and gallium (Ga)-doped phosphate glasses (PGs) are successfully obtained by the peroxidation method. The new glasses are characterized using Fourier-transform infrared spectroscopy (FTIR), Raman spectroscopy, X-ray diffraction, inductively coupled plasma-optical emission spectroscopy (ICP-OES), and pH measurements. A strong correlation between glass properties and their composition is found. The incorporation of Ga/Ce in the glass structure is confirmed by peak shifts in Raman and FTIR spectra. Degradation tests conducted in water confirm the soluble character of the PGs and reveal the influence of Ga and Ce on the degradation rate. Ga-doped glasses are found to be less soluble than Ce-doped ones (43%, 33%, 21%, and 16% of dry mass remained after 7 weeks for 7Ga, 5Ga, 5Ce, and 7Ce, respectively). Biological evaluation using ST-2 cells shows adequate cell response with a cell viability of 80% measured using the indirect contact method depending on the composition. The cell viability decreases with an increase in Ga content and increases with Ce content. The antibacterial character of Ga/Ce-doped PGs is confirmed by turbidity measurements against Escherichia coli and Staphylococcus carnosus. The novel Ce/Ga-doped PGs exhibiting antibacterial properties and biocompatibility reported here are interesting for tissue engineering and wound healing applications.
CRIS-Team Scopus Importer:2020-03-17
Keywords: antibacterial properties; cerium; gallium; ion release; medical applications; phosphate glasses

Phosphate glass fibres with therapeutic ions release capability–a review - Lapa, Agata; Cresswell, Mark; Jackson, Phil; Boccaccini, Aldo R. (Advances in Applied Ceramics, 2020)
Phosphate-based glasses (PBG) have low melting temperatures and can be obtained by melt-quenching and sol-gel methods. The most significant characteristic of PBG is their ability to dissolve completely in aqueous solution within different timeframes. This solubility can reduce the need for revision surgeries and makes PBG well-suited for soft tissue regeneration. Phosphate glass fibres (PGF) due to their geometry and volume–surface area ratio are the subject of a growing number of studies on resorbable composites. Medical applications include bone fixation devices, nerve tissue scaffolds and wound healing. PBG can be doped with various ions to enhance their biological, chemical and structural properties allowing the preparation of fibres with designed properties and with the ability to release biologically active ions upon degradation. The aim of this review is to look in detail at the influence of different dopants on PGF behaviour, both at a structural and biological level.
CRIS-Team Scopus Importer:2019-12-24
Keywords: bone; bone fixation devices; hard tissue regeneration; metal ions; Phosphate glass fibres; soft tissue regeneration; soluble glasses; therapeutic ions